Contractual issues for building information modelling (BIM)-based construction projects: An exploratory case study - Ahmad Huzaimi, Abd Jamil; Mohamad Syazli, Fathi (IOP Publishing, 2019)
Building Information Modelling (BIM) enables close collaboration among project stakeholders to visualize what is to be built in a simulated environment by identifying any potential design, construction or operational issues. Despite the fact of its well-documented benefits, the extensive integration of BIM throughout the project lifecycle remains sporadic. The conventional contracts used in the Malaysian construction industry were established before the development of BIM. As BIM becoming ingrain in the delivery process, the inadequacies of these existing contracts have become visible. This paper presents the results of an exploratory case study using Qualitative Content Analysis dedicated to a BIM project and discusses a procurement approach of BIM to establish the contractual context by addressing the legal and contractual impediments namely; intellectual property, liability and process related risks-allocation in a Malaysian public construction. This paper also outlines the reasons why the implementation of BIM will foster the evolution of integrated contract delivery methods.